Improving nutrition knowledge and nutrient intake through nutrition education for post-stroke survivors and their families - Faza, Farah; Lestari, Lily Arsanti; Setyopranoto, Ismail; Susetyowati, Susetyowati (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2024)
Background: Malnutrition among post-stroke survivors is 14-52%. Nutrition knowledge reinforcement will be beneficial for the survivors and family/caregivers to maintain their nutritional status and improve quality of life.Objectives: To examine the improvement of nutrition knowledge about nutrition management for post-stroke survivors, family, and caregivers as well as the improvement of nutrient intake and nutritional status among post-stroke survivors.Materials and Methods: This study used pre-experimental design and was conducted in Embung Tambak Boyo, Sleman District during August 2018. The subjects were post-stroke survivors, being members of Happy Embung, and signing the informed consent. Total subjects were 27 post stroke survivors with 27 family/caregivers of them. This study consisted of a series of activities, as follows: pre-test and baseline assessment, i.e., anthropometry, blood pressure, physical function, and dietary were measured in the 1st week, a series of nutrition education in the 2nd and 3rd week, post-test and endline assessment in the 4th week. The paired sample T-test was employed to compare the differences between baseline data collected during the first week of intervention, and endline data, gathered in the final week of intervention.Results: Most participants were male (89%) and aged 60 or older (82%). After two series of nutrition education, there were notable increases in nutritional knowledge score of the survivor and family/caregivers, body weight, BMI, HGS, and energy intake of the survivor (baseline vs. endline, mean ± SE: 6.5±0.6 vs. 7.0±0.6; 8.8±0.3 vs. 9.3±0.3; 67.8±1.9 vs. 68.6±1.9; 29.5±0.8 vs. 29.8±0.7; 26.1±2.0 vs. 26.8±2.0; and 1334.5±75.7 vs. 1389.1±95.0, all p<0.05). However, there was no significant improvement on MUAC, body fat total, protein, fat, and carbohydrate intake among the survivors.Conclusion: Nutrition education might enforce nutrition knowledge of post-stroke survivors and family/caregivers, as well as nutritional status improvement among the survivors.Keywords: Nutrition education; nutrient intake; nutrition status; post-stroke survivors